3D Scanning in Repairing Tractor and Automobile Parts and Units - N. M. Yunusbaev (Сельскохозяйственные машины и технологии)
The authors have found that the expenditures in the structure of the production cost of repairing machines depend not only on the cost of spare parts and materials, but also on the assessment accuracy of the technical condition of inspected parts. Research purpose To study the possibilities of 3D scanning technology, to improve the measuring accuracy of worn parts during fault finding, and to determine a rational way to restore them.Materials and methods The authors have carried out the entrance control using the Artec Eva Lite portable handheld 3D scanner with the Artec Studio software while finding faults in the worn crankshaft of the ZМZ409 engine. They have used the Geomagic Control X software product, which allows carrying out threedimensional analysis of the part and obtain highprecision measurements, determine the wear of mutual rubbing surfaces, the presence of microcracks, damage to internal cavities and dents in complexshaped parts. Basing on the conventional technology and reference recommendations, they plotted the route of the crankshaft restoration technology.Results and discussion The authors have compared the measurement results obtained using metrology instruments and reports in the Geomagic Control X program. They have found significant differences, especially in the amount of digital data. It has been determined that the measurement accuracy obtained from the instruments turned out to be lower. Worn connecting rods and main journals of the ZМZ409 engine crankshaft have been restored by electrocontact welding of filler materials according to the recommended application modes.Conclusions The research has revealed the possibility of using 3Dscan in the process of repair and restoration. The authors have proved that this method allows increasing the efficiency of fault finding, shorten its duration in 6 times, reduce the level of subjectivity of the technical condition assessment of inspected parts and reduce the complexity of the process by 30 percent. The authors have confirmed the high accuracy of measurements (up to 0.03 millimeters), owing to which the direct costs of filler materials can be reduced by 20 percent. On the basis of the 3D scanning results, the authors have proposed to form databases in the form of digital archives of parts by groups and brands for subsequent operational use.